For better or for worse: The long-term effects of postwar reconstruction on family formation - Mevlude Akbulut-Yuksel; Melanie Khamis; Mutlu Yuksel (Institute for the Study of Labor (IZA), 2013)
This paper provides causal evidence on the long-term legacies of postwar reconstruction and mandatory employment on women's family formation outcomes such as marriage, age at first marriage and divorce. We exploit city-by-cohort variation in the intensity of World War II reconstruction in Germany which determined the mobilization of women in the postwar era. We find that participation in the postwar reconstruction efforts increased the female's probability of being currently and ever married and marrying at younger ages. We also find that postwar mandatory employment had no differential effect on the divorce rates among the affected cohorts of women. These results are robust to the potential changes in the population composition, household income and demand for female labor and state-specific policies in postwar Germany.
Keywords: J12; J16; J21; J48; 330; postwar reconstruction; mandatory employment; marriage research